Anaesthetic Management of a Patient with Dermatomyositis and Valvular Heart Disease - Shrestha, GS; Aryal, D (Kathmandu University Medical Journal, 2013)
Dermatomyositis is an idiopathic inflammatory myopathy with involvement of muscle, skin and other organs. Valvular heart disease increases the risk of perioperative adverse cardiac events. Only a little information is available about the anaesthetic management of a patient with dermatomyositis and valvular heart disease. Here we considered combined spinal-epidural technique for total abdominal hysterectomy, minimizing the risk of delayed recovery from muscle relaxants, aspiration pneumonitis, arrhythmias and cardiac failure. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 100-102 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7355